Effect of endodontic sealers on bond strength of restorative systems to primary tooth pulp chamber - Ülkü Şermet Elbay; Gül Tosun (Elsevier, 2017)
Background/purpose: Although current literature suggests that root canal sealers affect the bonding ability of restorative systems to pulp chamber dentin of permanent teeth, primary teeth have not been investigated. This study intended to evaluate the microtensile bond strength (μTBS) of three restorative systems to pulp chamber dentin in primary teeth and to determine the effect of two different root canal sealers on the μTBS. Materials and methods: Ninety primary molars were used in this study. The teeth were randomly divided into three main groups according to canal sealers: (1) control (without sealer); (2) Metapex; and (3) zinc-oxide eugenol. The main groups were further divided into three subgroups depending on the coronal restorative system: (1) compomer (Prime Bond NT + Dyract EXTRA); (2) composite (Clearfil Tri-S Bond + Clearfil Photo Posterior); and (3) resin-modified glass ionomer (Fuji II LC). After restoration, the buccal wall of the pulp chamber was sectioned to obtain sticks (1 mm × 1 mm). The μTBS was then measured. Data were analyzed with two-way analysis of variance, followed by a posthoc test. The interfacial morphology of the bonded space was evaluated using scanning electron microscopy. Results: In the control group, a significant difference was observed only for the μTBS of the composite (P < 0.05). Compared with the control groups, Metapex and zinc-oxide eugenol significantly reduced the μTBS of restorative systems (P < 0.05). Conclusion: Composite materials seemed to bond to pulp chamber dentin in primary teeth with a higher strength than compomer and resin-modified glass ionomer. Metapex and zinc-oxide eugenol canal filling materials reduced the bond strength of all three restorative systems.